THE EVALUATION OF PHYSICS STUDENTS' PROBLEM-SOLVING ABILITY THROUGH MAUVE STRATEGY (MAGNITUDE, ANSWER, UNITS, VARIABLES, AND EQUATION) - Nikat, Rikardus Feribertus; Parno, .; Latifah, Eny (PEOPLE: International Journal of Social Sciences, 2021)
Problem-solving ability is very important to be developed in the process of learning physics especially in understanding the material of physics, both in concept, procedure analyses, and mathematical calculation. MAUVE strategy can help students as well as teachers in evaluating the extent to which students understand the concept of physics in accordance with the stages of problem-solving. The significance of this study are exploiting the way teachers to assess students' work in solving physics problems through MAUVE strategy and knowing physics students' problem-solving skills which were evaluated with the rubric developed by MAUVE. This paper applies descriptive quantitative research. The data collection uses test, observation, and interview. The result of this study is that MAUVE strategy facilitates teachers and students in evaluating problems on the physics material. Students can evaluate themselves about what deficiencies need to be improved in solving physics problems. For teachers, MAUVE is one of the easiest strategies to resolve problem-solving skills, so it needs to be evaluated for what needs to be improved. MAUVE strategy needs to be further developed on other topics of physics.